Application of box and wire brush as alternative tools in contemporary abstract batik pattern creation technique - Awang, Junaidi; Abdullah, Zamrudin; Mohammad Noh, Liza Marziana; Mohd Ghazali, Siti Aswani; Abdul Hamid, Haslinda (Faculty of Information Management, 2025)
Batik is a textile handicraft art that refers to the technique of creating fabric patterns by involving two main processes, namely wax-resist dyeing followed by the dyeing process. This study examines the innovation aspect of the creation technique from existing conventional methods such as the canting, copper stamp application, and silk screen printing to the application of alternative tools in generating design patterns, specifically using two tools, namely used boxes and wire brushes. The aim of this study is to demonstrate the application and potential of contemporary abstract design patterns produced through the use of these alternative tools, which are applied through practical methods. Additionally, it aims to enrich the study of innovative alternative batik creation techniques that can provide benefits and ideas to batik artisans or entrepreneurs exploring the potential of tools in the category of used tools or low-cost everyday tools, in line with the current trend of the dominance of contemporary abstract batik design preferences in Malaysia compared to traditional motif-laden designs featuring flora and fauna. The methodology of this study is based on artistic practice research, utilising Graham Wallas’s Creative Process Model (1926) to evaluate the outcomes of using alternative tools. This study hopes to demonstrate the potential and ideas in the diversity of innovative techniques in batik creation to be expanded to the batik artisan and entrepreneur community.